CONTENT STILISTICS ON INDONESIAN YOUTUBER VLOG - Aji, Fajar (Capture : Jurnal Seni Media Rekam, 2022)
As a video-sharing site, YouTube has evolved into a new platform for audio-visual content creation. This condition enables not only celebrities and corporations (television media) to create content and become YouTubers but also the general public to do so. This article seeks to describe how YouTubers' vlog contents are stylized in Indonesia. As the defining elements, form, and style are transformed into data to identify the resulting stylistics. This descriptive qualitative research uses a subjective approach. The interpretation analysis was conducted based on the results to verbally illustrate the form and style elements of the vlog contents of the ten most subscribed Indonesian Youtuber channels in 2020. The findings indicate that the forms and styles of Indonesian YouTubers' vlog contents result in authentic, dynamic, spontaneous, and distinctive stylistics. These stylistics can finally create a sense of intimacy and engage the audience in the delivered content.